The three sphinxes, and other poems - Viereck, George Sylvester, 1884-1962; Haldeman-Julius, E. (Emanuel), 1888-1951 (Salt Lake City, UT : Project Gutenberg, 2025)
"The three sphinxes, and other poems by George Sylvester Viereck" is a collection of lyric and dramatic poems written in the early 20th century. The book probes the tensions between erotic desire and spiritual idealism, drawing on myth, religion, and modern psychology to meditate on love, art, faith, and mortality. An opening essay frames the poems as (3z(Bcomplexes(3y (Brevolving around Eros, Jesus, Lilith, and Eve. The title poem stages a dialogue in the desert where facets of Love confront the sacred and the bestial; elsewhere, terse pieces weigh fate and biology, while longer monologues and ballads reimagine biblical and cultural figures to test moral codes. A fierce credo reduces human certainties to appetite and death; a visit from Christ to a Puritan town rebukes joyless piety; Faust tires of heaven and hell while yearning to fuse Helen and Marguerite; Eve speaks the long suffering of women; and tributes, elegies, and city-visions praise the stubborn life of art. Across love lyrics, satires, and visionary psalms, the collection moves between ecstasy and disenchantment, ending in stark addresses to God and man$1 (Bs frail, defiant will. (This is an automatically generated summary.)s
Release date is 2025-09-09
Tim Miller, Hendrik Kaiber and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: American poetry -- 20th century